Reducing greenhouse gas emissions in agriculture without compromising food security? - Frank, Stefan; Havlík, Petr; Soussana, Jean-Francois; Levesque, Antoine; Valin, Hugo; Wollenberg, Eva Karoline; Kleinwechter, U.; Fricko, Oliver; Gusti, Mykola; Herrero, Mario; Smith, P.; Hasegawa, Tomoko; et al. (2017)
The presentation addresses how reducing agricultural GHG emissions impacts food security, and what the trade-offs are.